Stabilization of polyaniline by the incorporation of magnetite nanoparticles (2012)
ABSTRACT: Nanocomposites obtained from the polymerization of aniline in the presence of nanoparticles of magnetite (Fe3O4) have been investigated in previous studies. However,there is a lack ofinformation available on the redox interaction of the nanoparticle/conductive polymer couple and the stability that such an oxide can give to the organic phase. In this work, Fe3O4 nanoparticles were incorporated into a PANi matrix by the in-situ oxidative polymerization method. A combination of X-ray diffraction, Mössbauer spectroscopy, transmission electronic microscopy, UV–visible spectroscopy as well as the cyclic voltammetric and Raman spectroscopy techniques, was used to understand the redox effect that the partially oxidized nanoparticles produced on the polymer. It was found that magnetite greatly stabilised PANi, mainly by enhancing the Leucoemeraldine/ Emeraldine redox couple and also by reducing the bipolaronic state